The Understanding of Peak Oxygen Uptake in Children Aged 8–16 - Wong, Simpson W. L.; Yu, Clare C. W.; Li, Albert M. (Frontiers in Pediatrics, 2021)
Objective: To examine the understanding of the concept peak oxygen uptake (peak VO2) among children and adolescents at different ages from a developmental perspective. Methods: A total of 549 children and adolescents aged 8 to 16 were recruited and instructed to fill in a 20-item Peak VO2Understanding Inventory developed with reference to the research literature on peak VO2. We presented the participants with twenty scenarios and asked them to indicate whether peak VO2 would “remain unchanged,” “increase,” or “decrease,” or that there was “insufficient information for a definite answer.” The cross-sectional data was analyzed by employing a series of ANOVA analyses and chi-square association tests. Additional statistical analyses were performed to examine the error patterns and if there were gender differences. Results: Except for the 8-year-old group, the overall accuracy rate did not improve with age. Age-related differences in the choice of answers (“increase,” “decrease,” “unchanged,” and “uncertain”) for determining the resulting peak VO2 after a change of antecedent were observed. Error analysis by item showed that prefactual thinking that is important to understand the concept was emerging rather than fully developed in our child and adolescent samples. Conclusion: The mastery of peak VO2 is not subject to age-related maturation but might demand the acquisition of specific logical reasoning skill such as perfactual thinking. Early introduction of peak VO2 and related concepts is advocated and should be emphasized on the reasoning rather than providing model answers in physical literacy education.